THU0297 Prevalence and Clinical Significance of Severe Flares in a Cohort of Systemic Lupus Erythematosus. (23rd January 2014) - López, R.; Erausquin, C.; Rodríguez-Lozano, C.; Naranjo, A.; Ojeda, S.; Francisco, F.; Quevedo, J. C.; Cáceres, L.; García-Bello, M.; Rúa-Figueroa, I.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a systemic autoinmune disorder of relapsing-remitting nature. However, we don´t have enough knowing about severe flare´s relevance on damage, severity or death in SLE patients. Objectives: To analyze the cumulative incidence and clinical significance of severe flares (SF) in a monocentric, well characterized SLE cohort. Methods: Cumulative clinical data were retrospectively collected at the moment of the last assessment. SF was defined using Selena-Sledai Flare Index (SFI) tool. Persistently active disease was not considered. SLICC/ACR/DI (SDI) was used to assess damage. Fisher exact test was used for qualitative variables and Kruskal-Wallis for quantitative ones. We compared patients with SF with patients without SF antecedents using bivariate analysis, and also analyzed the impact of SF on SLE-related mortality. Results: We studied 286 SLE patients (1997 ACR criteria); 3 patients were excluded by insufficient data about flare; 283 were finally included. Female: 91%; caucasian 94.5 %; mean age 48.5 (±13.3); mean SLE duration: 17.1 (±8.8) years; mean follow-up 14.3 (±10.2) years. Median SLE criteria: 6.0 (5.0-7.0); major organ involvement 49 %; class III or IV (OMS) lupus nephritis : 30%; hospitalization by SLE:64 %; median SLICC/ACR/DI 1.0 (0.0 2.0): 7.8 % of the patients had died at the study moment. Severe infection (SInf): 32% hospitalization by SInf : 30%. Cumulative treatment: 84% had received antimalarials at any time, 81%, corticosteroids (≥ 60mg/day: 45 %) and 54 % inmunosupressants; 272 (96.4%) patients had ≥1 flare, median 2 (IQR:1-3). Median SF:1.00 (IQI:0-2), (range: 0-13), mean: 1.4. Median SF per year:0.073 (IQR:0.00-0.17). SF was associated to more damage, Sinf, hospitalization by SInf, more number of hospitalization by infectionand number of SLE criteria (table1). Conclusions: In our SLE cohort, a history of severe flare was associated to dead, more damage and severe infection. Disclosure of Interest: None Declared